The Design and Development of a Web Based 2nd Hand Book Sale System for UUM - Tan, Aaron Eng Kiat (2003)
The purpose of this project was to design and develop a web based second hand or used book sale system called the Bexuum.com system for the Universiti Utara Malaysia (UUM) community. The second hand book web based system provides an exchange medium for UUM students and staff to sell out their used book. In addition, the web based system enables them to purchase used book at an agreeable price. The main functions of the system are browse book; manage book sales offering, review book, and rate bookseller. The system was developed using the object-oriented approach, which used Unified modeling Language (UML) as a modeling tool.